2013
DOI: 10.2111/rangelands-d-13-00015.1
|View full text |Cite
|
Sign up to set email alerts
|

Case Study: Adaptive Grazing Management at Rancho Largo Cattle Company

Abstract: Cattle Company (RLCC; lat 37°46′N, long 104°20′W) is 60 miles southwest of La Junta, Colorado. RLCC lies between 5,400 feet and 6,000 feet elevation and contains 14,020 acres in the shortgrass steppe ecoregion. Mean annual precipitation over the last 60 years was 11.4 inches. Approximately one-third of the ranch has mixed piñon-juniper and shortgrass prairie habitat around small canyons in the Dakota Sandstone and two-thirds of the ranch is open shortgrass steppe. RLCC consists mostly of loamy plains and sandy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Twothirds of 765 ranchers responding from across two western states and 15 ecoregions reported on-ranch use of rotational grazing strategies. This adoption rate confirms that ranchers do perceive social, economic, and/or ecological benefits which have not been documented in scientific comparisons of rotational and continuous grazing systems (Briske et al, 2011a;Grissom and Steffens, 2013;Teague et al, 2011Teague et al, , 2013.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Twothirds of 765 ranchers responding from across two western states and 15 ecoregions reported on-ranch use of rotational grazing strategies. This adoption rate confirms that ranchers do perceive social, economic, and/or ecological benefits which have not been documented in scientific comparisons of rotational and continuous grazing systems (Briske et al, 2011a;Grissom and Steffens, 2013;Teague et al, 2011Teague et al, , 2013.…”
Section: Discussionsupporting
confidence: 58%
“…Various classes of grazing strategies (e.g., continuous, rest rotation, and short duration) have been institutionalized and promoted via the academic community, conservation incentive funding programs, federal public grazing lands policies, and others (Briske et al, 2011b). Recent scientific syntheses have concluded that rotational grazing strategies of the manner and scale researched thus far provide no unique ecological or agricultural benefits in comparison with continuous grazing strategies (Briske et al, 2008(Briske et al, , 2011a These syntheses appear to conflict with experiential knowledge and perceptions of the successes of place-based, adaptively managed, rotational grazing strategies on working landscapes (Briske et al, 2011a(Briske et al, ,2011bGrissom and Steffens, 2013;Norton et al, 2013;Teague et al, 2011Teague et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…As opposed to traditional rotational grazing at low stock densities, managing stocking density in a flexible and dynamic way can enhance plant production and diversity (Provenza et al, 2003;Campbell et al, 2006) and should be encouraged. Such highly qualified management of stocking density can greatly benefit animal welfare and improve vegetation abundance and plant diversity (Grissom and Steffens, 2013;. Further research is needed on the relationship between stocking rate and livestock behavior and welfare under different environments and grazing regimes.…”
Section: Chronic Hungermentioning
confidence: 99%
“…Rotational Park et al, 2017 Global N/A N/A Infiltration declines and soil erosion increases as grazing intensity increases; high intensity grazing substantially negative for soil aggregate structure and infiltration Dadkhah and Gifford, 1980;Mulholland and Fullen, 1991;Thurow, 1991 BIOMASS BENEFITS REVIEW USA N/A N/A RG management increased ground cover and total biomass Barnes and Howell, 2013 Wyoming, USA N/A N/A RG management increased ground cover and total biomass Graham, 2014 Serengeti National Park, TZ vegetation to regrow before being grazed must often be variable in response to weather, level of defoliation, and timing of defoliation (Grissom and Steffens, 2013). These differences in grazing management regimes make them difficult to test in a formal, experimental setting.…”
Section: Locationmentioning
confidence: 99%
“…First, while the model assumes that increased stocking density automatically increases the level of defoliation of all plants, at certain levels an increase in stocking density may simply increase the likelihood that any particular plant will be defoliated (Teague et al, 2008). Second, one potential driver of the beneficial impacts of rotation was not considered here: many anecdotal reports of increased ranch productivity with rotational grazing include improved pasture composition (Grissom and Steffens, 2013). Parameterizing RPM to simulate multiple pasture species, while possible, constitutes a heavy data burden.…”
Section: Simulated Biomass and Animal Performance Benefitsmentioning
confidence: 99%